"Clickable" thiacalix[4]arene derivatives bearing polymerizable 1, 3-butadiyne fragments: synthesis and incorporation into polydiacetylene vesicles. Issue 50 (9th May 2016) - Burilov, Vladimir; Valiyakhmetova, Alsu; Mironova, Diana; Safiullin, Roman; Kadirov, Marsil; Ivshin, Kamil; Kataeva, Olga; Solovieva, Svetlana; Antipin, Igor
Abstract : Thiacalix[4]arene-functionalized polydiacetylene (PDA) vesicles showed selective colorimetric response toward several lanthanide ions. This approach can be a good basis for lanthanide express analysis. Abstract : p-tert -Butylthiacalix[4]arene derivatives in 1, 3- alternate stereoisomeric form bearing polymerisable 1, 3-butadiyne fragments on the one side and amino/carboxylic groups on another were synthesized using stepwise functionalisation. Calixarene 7 embedded in polydiacetylene nanoparticles showed a selective colorimetric response toward lanthanide ions.